Acupuncture Analgesia in Patients With Traumatic Rib Fractures: A Randomized-Controlled Trial - Liu, Chun-Ting; Hsieh, Ting-Min; Wu, Bei-Yu; Huang, Yu-Chuen; Shih, Chun-Han; Hu, Wen-Long; Tsai, Ming-Yen; Chen, Yung-Hsiang (Frontiers in Medicine, 2022)
Pain management for traumatic rib fracture is important to prevent complications and reduce associated comorbidities. This trial investigated the analgesic efficacy of acupuncture on traumatic rib fracture. Patients with traumatic rib fracture were randomly assigned to traditional acupuncture (TA), laser acupuncture (LA) or sham laser acupuncture (SLA) groups in a 1:1:1 ratio. The intervention was performed on days 1 to 3 after treatment allocation. The acupoints included bilateral LI4 (Hegu), SJ6 (Zhigou), ST36 (Zusanli) and GB34 (Yanglingquan). The primary outcome was Numeric Rating Scale (NRS) scores for pain after the intervention. Secondary outcomes included sustained maximal inspiration (SMI) lung volume, stress responses, the use of analgesics, and associated complications. Data were analyzed via one-way analysis of variance (ANOVA) with Scheffé’s post hoc testing or chi-squared testing. Of the 120 study participants, 109 completed all interventions and measurements. The primary outcomes, which indicated average pain intensity levels and pain while deep breathing, were both significantly lower in the TA and LA groups than in the SLA group after 2 treatments. No between-group differences were observed in SMI lung volume, stress response, analgesics use or associated complications. These findings suggest that TA and LA are safe and effective analgesic modalities for pain management for traumatic rib fracture.